HOW TO DESIGN PODCAST FOR LEARNING WITH THE RAPID PROTOTYPE MODEL - Hernawan, Asep Herry; Dewi, Laksmi; Fadlillah, Ahmad Fajar (Prodi Teknologi Pendidikan, 2021)
A podcast is a digital audio recording disseminated over the internet that can be transmitted, played, and downloaded directly to consumer media devices, including portable music players, computers, laptops, and smartphones. It can be categorized as an m-learning strategy for teaching and learning. It allows students to learn independently, easy to use, dynamic content meeting to listeners’ needs, and portable. The categories of using podcasts for learning are as sub-constitutional, supplemental, and integrated. Several things need to be considered in designing a podcast for learning covering its course’ objectives, students’ character, goal, type, writer, correlation to other teaching materials, a style used, duration, media, technology and material, sound used, the image included, and music. In designing a good podcast for learning, it is necessary to apply a systematic learning system's systematic procedure. This article discusses how to design podcasts for learning with The Rapid Prototype Model. This model is an instructional design method used to design and develop models with the stages of needs analysis, content analysis, determining objectives, constructing prototypes, utilizing prototypes, and installing and maintaining the system.